2012
DOI: 10.1167/iovs.11-9294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Palmitoylethanolamide on Aqueous Humor Outflow

Abstract: Our results demonstrate that PEA increases aqueous humor outflow through the TM pathway and these effects are mediated by GPR55 and PPARα receptors through activation of p42/44 MAPK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
(83 reference statements)
0
21
0
1
Order By: Relevance
“…Romano & Lograno () also showed a time‐dependent vasorelaxant response to anandamide and PEA in the bovine ophthalmic artery, but this effect was inhibited by a PPARα, but not a PPARγ, antagonist. Kumar et al () showed that PEA increases aqueous humour outflow in porcine eyes, which is inhibited by PPARα antagonism or knockdown.…”
Section: Physiological Responses To Cannabinoids Mediated By Pparsmentioning
confidence: 99%
See 1 more Smart Citation
“…Romano & Lograno () also showed a time‐dependent vasorelaxant response to anandamide and PEA in the bovine ophthalmic artery, but this effect was inhibited by a PPARα, but not a PPARγ, antagonist. Kumar et al () showed that PEA increases aqueous humour outflow in porcine eyes, which is inhibited by PPARα antagonism or knockdown.…”
Section: Physiological Responses To Cannabinoids Mediated By Pparsmentioning
confidence: 99%
“…Scuderi et al , ; De Novellis et al , ; Khasabova et al , ; Kumar et al , ; Romano and Lograno, ; Ambrosino et al , ; Citraro et al , ; Esposito et al , ; Borrelli et al , ; Hind et al , …”
Section: Introductionunclassified
“…In rat hippocampal organotypic cultures, PEA was able to reduce b-amyloid-evoked astrogliosis in a manner inhibited by PPARa, but not PPARg, antagonists [103]. PEA, in combination with the FAAH inhibitor URB597, enhanced trabecular meshwork aqueous humor outflow in porcine eyes in vitro [104]. This was not blocked by rimonabant, but was partially reversed by SR144528 or GW6471, a PPARa antagonist.…”
Section: Ppar Activation By Phytocannabinoids and Endocannabinoidsmentioning
confidence: 90%
“…One of these is N‐palmitoyl ethanol amide (PEA) an endogenous N‐acylethanolamine widely distributed in different tissues and having the characteristic of increasing its level after stress or injuries associated with neuropathic pain . The biochemical action of PEA involves multiple receptors and its good affinity for peroxisome‐proliferative receptor α (PPARα) and cannabinoid‐like G‐protein‐coupled receptors (GPR55 and GPR119) . The activation of PPARα culminates in switching off the nuclear factor kappa‐B (NF‐κB), blocking the proinflammatory mediators involved in neuropathic pain .…”
mentioning
confidence: 99%
“…14 The biochemical action of PEA involves multiple receptors and its good affinity for peroxisome-proliferative receptor α (PPARα) and cannabinoid-like G-protein-coupled receptors (GPR55 and GPR119). 15 The activation of PPARα culminates in switching off the nuclear factor kappa-B (NF-κB), blocking the proinflammatory mediators involved in neuropathic pain. 16 The concomitant stimulation by PEA of GPR55 and GPR119 reflects its influence on ion channels.…”
mentioning
confidence: 99%